Biosorption of Cd (II) from water using Citrobacter koseri - Hasan S.H.; Bhattacharjee B.N.; Ranjan D.; Talat M. (My University, 2025)
The potentiality of Citrobacter koseri for the removal of Cd (II) from aqueous solution through sorption was tested. The investigation was conducted in batch mode process and the effect of various parameters such as pH, initial Cd(II) concentration, temperature and biomass doses were studied. Thermodynamic parameters revealed that the sorption process was spontaneous, feasible and endothermic. Since the data fitted well to Langmuir model as compared to the Freundlich model this indicates the monolayer sorption on homogeneous surface of sorbent. Kinetics studies showed that the sorption was followed by the pseudo-second order rate expression. © 2008 Springer-Verlag.